Effects of Orgacids™ on growth performance, gut microflora and pH and meat cholesterol in growing pigs - Loh, Teck Chwen; Low, Y. S.; Chang, Y. K. (Universiti Putra Malaysia Press, 2004)
A total of 240 Large White x Landrace x Duroc postweaning piglets, 28to 32 days of age with the average body weight of 6.65kg were used in this study. The body weight, total live weight gain, total feed intake and feed conversion ratio were not significantly different. The control pigs had a higher number of faecal Enterobacteriaceae than OrgacidsTM pigs. The lactic acid bacteria (LAB) for the OrgacidsTM pigs was higher than the control pigs. The faecal pH for the OrgacidsTM pigs was lower than those of control pigs. The control pigs had a higher meat cholesterol concentration than the OrgacidsTM pigs. These results suggest that supplementation of organic acids have beneficial effects to the health of the pigs.